2021
DOI: 10.1002/cjce.24152
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aluminium acetate particles size on the gelation kinetics of polyacrylamide‐based gels: Rheological and molecular simulation study

Abstract: Inorganically crosslinked polymers have been intensively implemented for conformance control treatments in oil and gas wells at low temperatures (<90°C) because of their faster gelation time compared to organically crosslinked gels. Crosslinkers such as chromium acetate are known to be toxic, and aluminium‐based alternatives have been introduced. This study aims to investigate the impact of aluminium acetate (AlAc) particle size on the gelation kinetics of polyacrylamide (PAM)‐based gels at a pH of 5 and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition to its application in organic crosslinked polymer systems, molecular modelling techniques have been extended to the study of inorganic crosslinked polymer gel systems. Hamza et al [ 46 ] from Qatar University crosslinked polyacrylamide (PAM) with aluminium acetate (AlAc) and introduced bentonite as an additive in their study, aiming to enhance the stability of the gel system. They investigated in detail the effects of bentonite addition and AlAc particle size on the PAM/AlAc gel system and deeply explored the interaction mechanism between the crosslinker and bentonite by molecular simulation.…”
Section: Application Of Molecular Modelling Techniques To Different A...mentioning
confidence: 99%
“…In addition to its application in organic crosslinked polymer systems, molecular modelling techniques have been extended to the study of inorganic crosslinked polymer gel systems. Hamza et al [ 46 ] from Qatar University crosslinked polyacrylamide (PAM) with aluminium acetate (AlAc) and introduced bentonite as an additive in their study, aiming to enhance the stability of the gel system. They investigated in detail the effects of bentonite addition and AlAc particle size on the PAM/AlAc gel system and deeply explored the interaction mechanism between the crosslinker and bentonite by molecular simulation.…”
Section: Application Of Molecular Modelling Techniques To Different A...mentioning
confidence: 99%
“…Most in situ inorganically cross-linked systems are favorable at low to moderate pH conditions because of the fast gelation at high pH . Chromium­(III), cobalt­(II), aluminum­(III), titanium­(IV), and zirconium­(IV) are widely used for in situ gel applications as inorganic cross-linkers. …”
Section: Introductionmentioning
confidence: 99%
“…Molecular modelling revealed that AlAc particles are adsorbed on the bentonite surface, hindering their access to the polymer. [2] Evaluation of viscoelastic surfactant-based diverting agent during the chemical treatment of sandstone reservoirs Rasoul Nazari Moghaddam, Marcel van Doorn, Auribel Dos Santos, Hans Oskarsson, Kiernan Heck, Paul Ferm While the use of viscoelastic surfactants (VES) as diverting agents for limestone acidizing is widely known, the use of these non-damaging chemicals in sandstone stimulation is often overlooked. This study shows that combining acid stages with VES diverting agents is a feasible approach for sandstone formations despite having a lower calcite content.…”
mentioning
confidence: 99%
“…Furthermore, bentonite at low concentration can be used as a retarder of the crosslinking of PAM/AlAc without a significant impact on the gel strength. Molecular modelling revealed that AlAc particles are adsorbed on the bentonite surface, hindering their access to the polymer [2] …”
mentioning
confidence: 99%